Risk syndromes, clinical staging & DSM V - McGorry, P. (Die Psychiatrie, 2010)
While it has long been recognised that the need for care in psychiatry substantially precedes the point that a diagnosis can be made according to classical concepts, defining the initial characteristics of the early stages of the major psychiatric syndromes remains a controversial issue. Our current diagnostic systems do not acknowledge the complex evolution of the early stages of the major mental disorders, and thus where to set the boundary between mental health and ill-health, i.e. determining the „need for care“ and hence the range and sequence of interventions to be offered is one of the key questions facing psychiatry today. What is needed is a heuristic strategy that aims to clarify as early as possible which people experiencing emotional and behavioural disturbances are at specific risk of persistent and disabling mental illness, and the sequence of established and novel therapeutic strategies that is most likely to achieve remission of their current symptoms and reduce the risk of persistence and recurrence. Since the initial operationalization of the clinical criteria denoting ultra-high risk for transition to psychosis 15 years ago, there has been substantial progress in confirming their predictive validity, and demonstrating that the risk that they confer can be reduced by psychosocial and drug therapies. This research has led to the idea of the “common risk syndrome” which precedes progression along the trajectories to more specific target syndromes such as the mood disorders or schizophrenia. Here, I propose that there is a need to research and operationalise criteria for an initial syndrome linked to the need for care of the simplest type, and to clearly define criteria that constitute the “common risk syndrome”. Research towards these goals is crucial not only to allow the selection the safest, most effective treatments appropriate for a particular stage of illness, but also for the ordering of the confusing array of disturbances seen during the development of mental illness into something resembling a clinicopathological approach.
Keywords: Clinical staging; early intervention; risk syndrome; psychosis; schizophrenia; mood disorder